An evaluation of risk management strategies and their operational effectiveness among small and medium enterprises in Mukono Municipality - Evalyne Kyomugisha (Uganda Christian University, 2025)
The study aimed at evaluating risk management strategies and their operational effectiveness among small and medium enterprises in Mukono Municipality. In particular, it focused on; examining the relationship between risk identification and operational effectiveness of SMEs, establishing the relationship between risk assessment and operational effectiveness of SMEs, and exploring the relationship between risk mitigation and operational effectiveness of SMEs in Mukono Municipality. Furthermore, the study was conducted using a cross-sectional survey research design, where quantitative research approach was also employed. A sample size of 133 SMEs operating in Kauga, Mukono Municipality was selected using simple random sampling method although 120 of them responded to the study. Data was collected using questionnaires and later analysed using SPSS. The ethical considerations while collecting data were fully considered by the researcher. The study findings established that risk identification (r = .866**, p< .05), risk assessment (r = .892**, p< .05), and risk mitigation (r = .885**, p< .05) each have a strong positive and significant influence on the operational effectiveness of SMEs in Mukono Municipality, with effective risk identification enhancing proactive management and employee involvement, thorough risk assessment improving decision-making, resource allocation, and adaptability, and comprehensive risk mitigation strengthening resilience, reducing disruptions, and ensuring operational and financial stability. Finally, the study recommended that SMEs in Mukono Municipality strengthen formal risk documentation, consistently adopt standardized risk assessment frameworks, integrate assessment findings into strategic planning, expand the use of financial protection tools like insurance and hedging, and leverage advanced technology for early risk detection and prompt mitigation, thereby enhancing operational effectiveness, resilience, and long-term financial stability.
Undergraduate Research